ESP VIRTUAL LEARNING MEDIA EVALUATION: A CASE OF ENGLISH FOR RESTAURANT WORKERS - Muhamad Nova (ETERNAL (English, Teaching, Learning and Research Journal), 2021)
The development of technology recently demands a shift in the English language teaching and learning process, and to support the independence of language learning, virtual learning becomes an option to bridge the need for technology integration and open-learning access from the internet. This research aimed at finding out the learning media evaluation for teaching English for restaurant workers through virtual learning, i.e. video, podcast, virtual simulation, and PowerPoint presentations. This research was carried out by conducting qualitative research. The data were collected using questionnaires to 57 students in a vocational education institution and an interview with several selected students to clarify and to confirm their unclear statements on the questionnaire. The data were then analyzed by calculating the frequency of students’ responses and classifying the responses toward the learning media application in virtual learning. As a result, it was found that video becomes the most preferable learning media and PowerPoint Presentations become the least preferable learning media in virtual learning for English for restaurant workers. The results also indicated that the mode of the video was more attractive and understandable since it could combine both audio and visual aids in the learning process, and support the students’ skill enhancement. Meanwhile, the single-mode PowerPoint Presentations were less attractive for the students and led them to boredom. Henceforth, the English teachers and lecturers who teach English for Specific Purposes are suggested to provide more video simulations on virtual learning platform to support the engagement of the teaching and learning activities.